Mirror‐Image Packing Provides a Molecular Basis for the Nanomolar Equipotency of Enantiomers of an Experimental Herbicide. (26th September 2016) - Bisson, Claudine; Britton, K. Linda; Sedelnikova, Svetlana E.; Rodgers, H. Fiona; Eadsforth, Thomas C.; Viner, Russell C.; Hawkes, Tim R.; Baker, Patrick J.; Rice, David W.
Abstract: Programs of drug discovery generally exploit one enantiomer of a chiral compound for lead development following the principle that enantiomer recognition is central to biological specificity. However, chiral promiscuity has been identified for a number of enzyme families, which have shown that mirror‐image packing can enable opposite enantiomers to be accommodated in an enzyme's active site. Reported here is a series of crystallographic studies of complexes between an enzyme and a potent experimental herbicide whose chiral center forms an essential part of the inhibitor pharmacophore. Initial studies with a racemate at 1.85 Å resolution failed to identify the chirality of the bound inhibitor, however, by extending the resolution to 1.1 Å and by analyzing high‐resolution complexes with the enantiopure compounds, we determined that both enantiomers make equivalent pseudosymmetric interactions in the active site, thus mimicking an achiral reaction intermediate.